The Appropriation of a Confessional Saint: The Image of Josaphat Kuntsevych in Engravings from Basilian Monasteries in the Second Half of the 18th Century - Fedyshyn, Nataliia (Lietuvos istorijos studijos, 2025)
This article explores how the image and cult of Josaphat Kuntsevych were appropriated by Basilian monasteries in the second half of the 18th century to shape the Uniate confessional identity within the Ukrainian territories of the Polish-Lithuanian Commonwealth. Through an analysis of Basilian-produced engravings, such as The Apotheosis of the Virgin of Pochaiv, and depictions alongside the miraculous icons of Terebovlya and Piddubtsi, the study demonstrates how Josaphat’s martyrdom was visually framed to reinforce Uniate religious and cultural narratives. The Basilians employed iconography, relics, and commemorative rituals not only to promote Kuntsevych’s veneration but also to position him as a confessional saint, representing the distinctiveness and confessional character of the Uniate Church. The article suggests that these efforts may have contributed to elevating Josaphat’s role within Uniate devotional practices and to shaping a more defined religious identity in the Ruthenian Basilian Province.